Analyzing Significance of Islamic Public Sphere: Study Case Jakarta 2016-2017 - Faiz Hosainie Rafsanjanie (Pascasarjana UIN Raden Mas Said Surakarta, 2025)
This research contains a discussion of the political case of the Islamic Public Sphere in Jakarta in 2016-2017. Taking the case of the Islamic Defenders Front (FPI) as a case study that will be examined in relation to the Islamic public sphere in Jakarta. The analysis of this study uses a qualitative method with data analysis through content, and a theory in the form of the Public Sphere by Jürgen Habermas. The results of the study show that the Islamic Defenders Front (FPI) is part of the Public Sphere in Jakarta in the 2016-2017 period, which greatly influences the government's decisions in determining the direction of the law in Indonesia.